EVALUATION OF BIOPOLYMER-BASED TRICHODERMA AND ACTINOMYCETES AGAINST WILT AND ROOT ROT COMPLEX OF SAFFLOWER (Journal of Plant Disease Sciences, 2025)
Safflower (Carthamus tinctorius) is an annual oilseed crop valued for its high-quality oil used in food, cosmetics, and industrial applications. Native to the Mediterranean region, safflower is now widely cultivated, with Maharashtra being a key producer in India. However, its production is significantly impacted by wilt disease, caused by Fusarium oxysporum f. sp. carthami, and root rot, caused by Macrophomina phaseolina, both of which lead to plant mortality, reduced seed yield, and inferior oil quality.This study focuses on the biological management of these diseases using biopolymer-based Trichoderma and actinomycetes. In in vitro experiments, biopolymer-based Trichoderma harzianum exhibited the highest inhibition of Fusarium oxysporum (mean colony diameter: 27.00 mm), followed by Trichoderma harzianum (42.30 mm). Similarly, Macrophomina phaseolina was significantly suppressed by Trichoderma harzianum (29.33 mm) and Trichoderma asperellum (30.33 mm), which performed at par, followed by Trichoderma koningii (34.33 mm) and biopolymer-based Trichoderma harzianum (47.50 mm).Field studies demonstrated that seed treatment with biopolymer-based Trichoderma at 10 ml/kg seed combined with soil application at 100 ml/5 L water per plot significantly reduced wilt and root rot incidence compared to other bioagents.
Keywords: Safflower; Wilt; Fusarium oxysporum; Macrophomina phaseolina; Trichoderma; Bioagents